Infusing equity in continuous improvement: supporting equity-focused leadership development in Columbus City Schools - Molle, Daniella; Sebenoler, Mickie; Eslinger, James C.; Agnes, Diane; Halverson, Richard (Frontiers in Education, 2025)
IntroductionThis paper is a case study of equity-centered continuous improvement that informed school leader professional learning. The work is a collaboration between researchers and district leaders in Columbus City Schools, USA. The continuous improvement process took place in the context of a multi-year, grant-funded initiative aimed at expanding school leaders’ capacity to advance equity in their buildings.MethodsOur findings are based on a thematic analysis of qualitative data that include interviews, field notes, and artifacts.ResultsWe highlight three social conditions that made the improvement work possible: a district-wide focus on equity, a culture of learning, and partnerships with external organizations. We explore in detail two examples of continuous improvement in the district, both related to school leader professional learning. We shed light on factors that hindered the district-wide use of continuous improvement in the district, including the absence of guidance on continuous improvement and the emerging nature of the collaboration among principal supervisors and coaches across the district.DiscussionThis work contributes to the field’s understanding of what equity-focused continuous improvement can look like. Our findings suggest that equity-centered continuous improvement encompasses equity-focused goals that aim to address disparities in students’ school experiences, and equity-focused processes that cultivate trust with school leaders and position them as capable learners and agents of change.